Novel quinizarin spray-dried nanoparticles for treating melanoma with photodynamic therapy - Gobo, Graciely Gomides [UNESP]; Piva, Henrique Luis; Tedesco, Antonio Claudio; Primo, Fernando Lucas [UNESP] (Elsevier, 2022)
Melanoma is the most aggressive skin cancer. Moreover, it resists most of the currently available therapeutic protocols that aim to control its lethal progression. Photodynamic therapy (PDT) is a well-established photoprocess that can be used as co-adjuvant treatment to classic cancer treatment and surgery. Indeed, PDT is a minimally invasive procedure that exerts photoinduced and selective cytotoxicity against some types of cancer, including less aggressive types of skin cancer. Quinizarin (QZ), a dye, has been employed as a photosensitizer in PDT. However, this molecule is highly hydrophobic, which prevents its direct application under physiological conditions. In an attempt to solve this problem, we have prepared a novel Whey Protein and polymethyl methacrylate QZ-based nano-drug delivery system (QZ-PP-NP) by the layer-by-layer emulsion method combined with nanospray drying and characterized it in terms of size, particle distribution, zeta potential, and morphology. Then, we conducted biological tests on the cell lines fibroblastoids (NIH-3T3) and cancerous cells of melanocytic origin (B16-F10) in vitro, to find that application of QZ-PP-NP and PDT decreased cell viability to less than 5 %.
Keywords: Melanoma; Nanoencapsulation; PDT; Quinizarin; Spray-drying